1991
DOI: 10.3171/jns.1991.75.2.0234
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of perfused adrenal medullary tissue into the caudate nucleus of patients with Parkinson's disease

Abstract: The authors report results obtained in 20 severely affected patients with Parkinson's disease (Grade IV or V) who received an autotransplant of perfused adrenal medullary tissue. This study seems to indicate that these autoimplants can improve the parkinsonian symptomatology and induce amelioration in the patients' performance of routine activities. All the symptoms analyzed showed improvement, although it differed in intensity and time of onset. Moreover, this improvement was accompanied by a reduction in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 29 publications
0
13
0
2
Order By: Relevance
“…62,[66][67][68][69][70] There were 52 articles for adrenal medullary transplantation, but the review includes only the 9 that met criteria. [71][72][73][74][75][76][77][78][79] For human fetal mesencephalon transplantation, 19 papers were found and all were included. 13,75,[80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] Once the evidence regarding all the articles reviewed was classified, each working group summarized all the collected data and indicated the quality of evidence of all citations contributing to their recommendations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…62,[66][67][68][69][70] There were 52 articles for adrenal medullary transplantation, but the review includes only the 9 that met criteria. [71][72][73][74][75][76][77][78][79] For human fetal mesencephalon transplantation, 19 papers were found and all were included. 13,75,[80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] Once the evidence regarding all the articles reviewed was classified, each working group summarized all the collected data and indicated the quality of evidence of all citations contributing to their recommendations.…”
mentioning
confidence: 99%
“…Three ideas for modified protocols have evolved from these studies: first, special perfusion techniques aimed at increasing cell survival 75 ; second, the addition of trophic factors or peripheral nerve cotransplants to enhance cell survival; and third, the grafting of fetal adrenal medullary cells. Cotransplantation procedures combining adrenal medullary tissue with peripheral nerve fragments have been performed in two small series (<5 subjects each), and in each, selected patients improved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] Fetal cholinergic implants have also reversed cognitive deficits of maze learning in rats with lesions of the fimbria-fornix, in an animal model of Alzheimer's disease. 11,12 In addition, adrenal tissue has been used as an alternative source of dopamine producing cells, 13,14 but does not appear to ameliorate deficits observed in animal models of Parkinson's disease. 15,16 More recent efforts have focused on the development of cultured or genetically modified cells that can serve as replacement cells for degenerating neurons in neurodegenerative disorders, or the use of cells capable of releasing specific trophic factors in brain-damaged regions.…”
Section: Nerve Growth Factor Expression In Brain Transplantsmentioning
confidence: 99%
“…In case of PD patients, they were grafted mainly into the putamen bilaterally, using between three to five donors per hemisphere (Lindvall 1992, Freed 1992. There were also reported cases of caudate nucleus transplantation (Henderson 1991, Molina 1991, Lopez-Lozano 1991, Spencer 1992 and of putamen and substantia nigra (SN) simultaneous transplantation (Mendez 2002). Several open-label trials reported clinical benefit and long-term graft sur-vival.…”
Section: Introductionmentioning
confidence: 99%